Characteristic Parameters Analysis on Breast Shape for Moulded Bra Cup and Bra Structure Design (Journal of Fiber Bioengineering and Informatics, 2014)
At present, bra enterprises usually use under bust girth and bust differences to design bra pattern.These kind of bras do not consider the differences of breast shapes and therefore cannot not satisfy thedemands of fit and comfort of different breasts. This paper firstly elaborates on the effect analysis ofbra wearing to discover the differences then verifies the importance of breast characteristic parameters.Then a three dimensional laser scanner is used to measure the size of 75B of young female breast shapeto collect data. In order to analyze breast shape change rule for moulded bra cup and bra structuredesign, basic statistics analysis, factor analysis and cluster analysis were conducted for breast data.Finally, six major characteristic parameters on breast height, bust external side slope, breast depth,under bust depth, biacromial breadth and center front point-bust inner point length were extracted forbra structure design. Also, cluster analysis was used to divided breast shapes into three shapes. Theresults of the paper can be used for providing technical parameters and theoretical basis for further studyof bra structure design. It also explores a new direction of the development of tailored moulded bra cupand bra structure design.